2013
DOI: 10.1017/s2045796013000206
|View full text |Cite
|
Sign up to set email alerts
|

Linking abuse and recovery through advocacy: an observational study

Abstract: Aims. High numbers of psychiatric service users experience domestic violence, yet limited interventions exist for these victims. We piloted a domestic violence intervention for community mental health services to explore the feasibility of a future cluster randomized controlled trial. Methods. Quasi-experimental controlled design within five Community Mental Health Teams (three intervention and two control teams). The intervention comprised domestic violence training for clinicians' and referral to domestic vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 45 publications
0
36
0
5
Order By: Relevance
“…of the power dynamics of DVA relationships involving coercive control), and AUTHOR ACCEPTED MANUSCRIPT Lancet Psychiatry http://www.thelancet.com/journals/lanpsy/onlineFirst lack of clarity about the role of mental health professionals in addressing DVA. 99,100 A meta-synthesis of qualitative studies involving mental health service users found that DVA victims want mental health professionals to acknowledge and/or validate their disclosures of domestic violence in a nonjudgemental and compassionate manner. 50 Some service users reported that their disclosures were not taken seriously and they felt blamed by professionals, which was unhelpful and associated with persistent symptoms (see also above).…”
Section: Identifying Victims Of Vaw In Mental Health Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…of the power dynamics of DVA relationships involving coercive control), and AUTHOR ACCEPTED MANUSCRIPT Lancet Psychiatry http://www.thelancet.com/journals/lanpsy/onlineFirst lack of clarity about the role of mental health professionals in addressing DVA. 99,100 A meta-synthesis of qualitative studies involving mental health service users found that DVA victims want mental health professionals to acknowledge and/or validate their disclosures of domestic violence in a nonjudgemental and compassionate manner. 50 Some service users reported that their disclosures were not taken seriously and they felt blamed by professionals, which was unhelpful and associated with persistent symptoms (see also above).…”
Section: Identifying Victims Of Vaw In Mental Health Servicesmentioning
confidence: 99%
“…114 A small pilot in community mental health teams in South London suggests that DVA advocates integrated within teams, in addition to dedicated time for training, improve rates of identification of DVA and outcomes for individual victims with fewer unmet needs and lower levels of abuse at 3 months follow-up. 100 Echoing findings that improving mental health service responses to DVA requires more than training, an audit conducted in New Zealand found that although the proportions of child and adulthood sexual and physical abuse included in formulations and treatment plans increased after the introduction of a trauma policy and training programme, actual interventions remained low. 115…”
Section: Identifying Victims Of Vaw In Mental Health Servicesmentioning
confidence: 99%
“…In the UK, for example, a cross-sectional survey of 131 psychiatrists and psychiatric nurses found that although psychiatrists reported significantly greater knowledge about the nature and impact of DV than did psychiatric nurses, they felt less ready to use their knowledge to assess and manage service users' experiences of abuse (Nyame et al, 2013). A pilot study conducted in UK Community Mental Health Teams (CMHTs) found, however, that an intervention which combined DV training for clinicians and the implementation of a referral pathway to DV advocacy for service users improved rates of identification and referral among mental health professionals in addition to improved self-reported DV knowledge, attitudes, and behaviours (Trevillion et al, 2014a). An evaluation of an intervention aimed at achieving organisation-wide changes in responses to DV at two UK mental health care organisations ("Promoting Recovery In Mental Health", http://www.kcl.ac.uk/ioppn/depts/hspr/research/CEPH/wmh/projects/A-Z/Promoting-Recovery-in-Mental-Health-(PRIMH).aspx) including through the development of DV policies and competency frameworks, mentoring managers and senior practitioners to become DV champions, delivering training to frontline professionals and train-the-trainers, is currently underway.…”
Section: What Are the Barriers To Mental Health Professionals Identifmentioning
confidence: 99%
“…There has been limited research, however, on interventions for mental health service users with experiences of DV. This review identified three relevant studies: two before-and-after studies conducted in the USA and one quasi-experimental pilot study conducted in the UK (Frueh et al, 2009, Lu et al, 2009, Trevillion et al, 2014a. Although neither before-and-after study was aimed specifically for mental health service users with experiences of DV, both samples included participants with experiences of DV.…”
Section: Interventions For Service Users Experiencing Domestic Violencementioning
confidence: 99%
See 1 more Smart Citation